Development and characterization of dilutable self-microemulsifying premicroemulsion systems (SMEPMS) as templates for preparation of nanosized particulates - Lin SF (Dove Medical Press, 2013)
Shen-Fu Lin,1 Ying-Chen Chen,2 Hsiu-O Ho,2 Wei-Yu Huang,2 Ming-Thau Sheu,2,3 Der-Zen Liu1,4 1Graduate Institute of Biomedical Materials and Tissue Engineering, College of Oral Medicine, 2School of Pharmacy, College of Pharmacy, Taipei Medical University, Taipei, Taiwan; 3Clinical Research Center and Traditional Herbal Medicine Research Center, Taipei Medical University Hospital, Taipei, Taiwan; 4Center for General Education, Hsuan Chuang University, Hsinchu, Taiwan Abstract: The utilization of self-microemulsifying premicroemulsion systems (SMEPMS) as templates for preparing poorly water-soluble compounds in the nanosized range represents a promising strategy. Fenofibrate was formulated with n-butyl L-lactate, Tween 80, and a number of cosurfactants (ethanol, 1-propanol, and PEG 600), diluted with the water phase (either water or saccharide solution) and then subjected to a freeze-drying (FD) process to obtain SMEPMS nanosized particulates. Results demonstrated that the particle size after resuspension of these FD SMEPMS nanosized particulates in water was too large, so the addition of saccharide solutions (lactose, mannitol, glucose, sucrose, and trehalose) as the solid carrier to prevent particles from aggregating seemed to be necessary and workable due to steric hindrance and repulsion. However, instability of these resuspended FD nanosized particulates after 30–90 minutes still occurred, and the addition of 0.5% sodium lauryl sulfate in the resuspending medium was able to retard the aggregation and maintain the particle size within the nano-range. Evaluation by scanning electron microscopy and X-ray powder diffraction also confirmed the results. It was concluded that using an SMEPMS formulation with PEG 600 as the cosurfactant, and in the presence of a suitable saccharide as an anticaking agent and FD process were able to produce fenofibrate nanoparticles. Keywords: fenofibrate, saccharides, freeze-drying, nanoparticles